The Meaning of Traditional Households in Simalungun Language - Surip, Muhammad; Pujiono, Mhd.; Dewi, Nora Ronita (Talenta Publisher, 2019)
This study is aimed to describe the component of meaning, the role of semantic traditional household appliances in Batak Simalungun language. Qualitative descriptive method is used in this research. The data are words that contain the meaning field of traditional household appliances in Batak Simalungun language by using noted techniques. The sources of data are Simalungun Batak language spoken by native speakers. Besides 24 kinds of lexical and collocative meaning, the results of the research are also shown some traditional household appliances in Batak Simalungun language, there are: 6 household tools which is made of woven, 8 are made of wood, 6 are made of metal, 3 are made of stone, and 1 is made of yarn.